Prenatal diagnosis of congenital lobar fluid overload - Pei-Shan Tsai; Chih-Ping Chen; Dao Chen Lin; Yu-Peng Liu (Elsevier, 2017)
Prenatal congenital lobar fluid overload (CLFO), which was first described by Ramsay and Byron, is identical to postnatal congenital lobar overinflation. It is characterized by progressive lobar overexpansion that compresses the other adjacent lung lobes. The underlying cause can be an intrinsic cartilaginous abnormality or an extrinsic airway compression. It may be associated with cardiovascular anomalies in 12%-14% of cases and affects males more frequently than females. Most cases are diagnosed postnatally, but early antenatal diagnosis and sequential follow-up are attempted for early treatment, if clinically indicated. This article provided a thorough review of CLFO, including prenatal diagnosis and differential diagnoses, as well as comprehensive illustrations of the perinatal imaging findings of CLFO. Prenatal diagnosis of fetal lung lesions should include CLFO in the differential diagnosis and prompt investigation for associated anomalies.